2007
DOI: 10.1021/pr0704534
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Endogenous Peptides in Human Synovial Fluid by NanoLC−MS:  Method Validation and Peptide Identification

Abstract: Synovial fluid potentially contains markers for early diagnosis and disease progression in degenerative joint diseases such as osteoarthritis. Here, a method is described for profiling endogenous peptides in human synovial fluid, using ultrafiltration, solid-phase extraction, nanoscale liquid chromatography, and high-resolution mass spectrometry. Synovial fluid is characterized by its high viscosity, caused by the presence of the lubricant hyaluronic acid. The method proved to be capable of eliminating the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 43 publications
(78 reference statements)
8
47
0
Order By: Relevance
“…aggrecan, heparin sulfate, and cartilage oligomeric matrix protein) (55,56). Lubricin is a mucin-like glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…aggrecan, heparin sulfate, and cartilage oligomeric matrix protein) (55,56). Lubricin is a mucin-like glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…The high resolving power (>150,000) and excellent mass accuracy (specified as $2-5 ppm, but demonstrated to be as low as 0.2 ppm under favorable conditions) (Makarov et al, 2006a,b), significantly reduce false positive peptide identifications in bottom-up protein analyses (Adachi et al, 2006;Charneau et al, 2007;Dave et al, 2007;de Souza, Godoy, & Mann, 2006;Forner, Arriaga, & Mann, 2006;Graumann et al, 2008;Hanke et al, 2008;Hoopmann, Finney, & MacCoss, 2007;Kamphorst et al, 2007;Li et al, 2007b;Lu et al, 2007Lu et al, , 2008Manes et al, 2008;Mayampurath et al, 2008;Park et al, 2008;Scherl et al, 2008;Scigelova & Makarov, 2006;Shi et al, 2007;Swatkoski et al, 2007Swatkoski et al, , 2008Thevis et al, 2007b;Usaite et al, 2008;Venable et al, 2007;Wilson-Grady, Villén, & Gygi, 2008;Wisniewski et al, 2007;Zougman et al, 2008), and improve the accuracy of de novo interpretations of MS/MS spectra (DiMaggio et al, 2008;Ford et al, 2008;Frank et al, 2007;Scigelova & Makarov, 2006;Yates et al, 2006). The LTQOrbitrap has also been used to analyze intact small (3-10 kDa) (Bredehöft, Schänzer, & Thevis, 2008;Thevis et al, 2006a;Thevis, Thomas, & Schänzer, 2008b), medium (10-25 kDa) (Macek et al, 2006;…”
Section: Introductionmentioning
confidence: 99%
“…Or does lubricin fragmentation patterns in OA or RA differ from those in healthy individuals? Recent studies reported the fragment of lubricin in SF (Gobezie et al, 2007;Kamphorst et al, 2007). In the work of Kamphorst et al, they found two lubricin C-terminal fragments (R 1285 PALNYPVYGETTQV 1299 and D 1373 QYYNIDVPSRTA 1385 ) in OA SF but not in healthy SF (Kamphorst et al, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies reported the fragment of lubricin in SF (Gobezie et al, 2007;Kamphorst et al, 2007). In the work of Kamphorst et al, they found two lubricin C-terminal fragments (R 1285 PALNYPVYGETTQV 1299 and D 1373 QYYNIDVPSRTA 1385 ) in OA SF but not in healthy SF (Kamphorst et al, 2007). In the current study with enriched RA synovial lubricin, the first sequence (1285-1300) was found distributed throughout the gel; while the second sequence (1373-1385) was only detected in area 3 and 5, areas lower than the lubricin area ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation